2011
DOI: 10.2105/ajph.2011.300201
|View full text |Cite
|
Sign up to set email alerts
|

Using the Tax System to Promote Physical Activity: Critical Analysis of Canadian Initiatives

Abstract: In Canada, tax incentives have been recently introduced to promote physical activity and reduce rates of obesity. The most prominent of these is the federal government's Children's Fitness Tax Credit, which came into effect in 2007. We critically assess the potential benefits and limitations of using tax measures to promote physical activity. Careful design could make these measures more effective, but any tax-based measures have inherent limitations, and the costs of such programs are substantial. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…mandated limits), subsidies for providers, tax credits and direct transfers as instruments that could be used, but found no evidence to support the efficacy of these. Recent initiatives in Canada have involved tax credits to reduce the costs to families of organized physical activity and sales tax exemptions on sport and exercise equipment (von Tigerstrom et al, 2011). The limitations of these are that they give partial price reductions and are inequitable if the credits are non-refundable and cannot be used by persons below the income-tax threshold (Spence et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…mandated limits), subsidies for providers, tax credits and direct transfers as instruments that could be used, but found no evidence to support the efficacy of these. Recent initiatives in Canada have involved tax credits to reduce the costs to families of organized physical activity and sales tax exemptions on sport and exercise equipment (von Tigerstrom et al, 2011). The limitations of these are that they give partial price reductions and are inequitable if the credits are non-refundable and cannot be used by persons below the income-tax threshold (Spence et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, Nordstrom and Thunstrom [92••] simulated the impact of potential tax reforms with the intent to increase fiber intake on food consumption across different household categories and found that among seniors and families without children, reforms would lead to increases in fiber with concurrent increases in added sugar and fat intake; however, among families with children, the reforms would lead to small increases in fiber with concurrent reductions in the unhealthy nutrients. Finally, von Tigerstrom et al [93] provided an analysis of major tax reforms in Canada to improve physical activity, including income tax exemptions for organized sports and sales tax reductions on items, such as children's bicycles and footwear. The authors noted that major weaknesses included delayed benefits from income tax incentives and unintended increases of sales tax on other items.…”
Section: Policy Issuesmentioning
confidence: 99%
“…Refundable tax credits are available in Saskatchewan and Ontario which allow individuals to receive a refund even if they do not owe any income tax. Saskatchewan in particular allows individuals to claim a credit for the full amount of fees paid up to $150 per eligible child, rather than a percentage of the lowest federal income tax rate (Tigerstrom, Larre and Saunder 2011).…”
Section: Children's Fitness Tax Creditmentioning
confidence: 99%